Trabectedin in patients with pre-treated advanced soft tissue sarcoma: a retrospective single center analysis - Koseła, Hanna; Wiater, Katarzyna; Świtaj, Tomasz; Klimczak, Anna; Kamycka, Agnieszka; Falkowski, Sławomir; Ługowska, Iwona; Rutkowski, Piotr (Contemporary Oncology/Współczesna Onkologia, 2011)
Background : Trabectedin is a new cytotoxic drug registered in 2007 for therapy of advanced soft tissue sarcomas in case of failure of treatment with anthracyclines and ifosfamide or in patients who are not eligible for this kind of treatment. Pre-registration studies showed its efficiency in therapy of advanced soft tissue sarcomas. The aim of the study was to analyse the results of trabectedin therapy in patients with advanced soft tissue sarcoma of selected histological subtypes treated in one oncological centre. Material and methods : We retrospectively analysed 26 patients treated with trabectedin for advanced soft tissue sarcomas, in the period from 04.2008 to 03.2011. Thirteen patients were diagnosed with leiomyosarcoma, 10 patients with liposarcoma, 2 patients with synovial sarcoma, 1 with pleomorphic sarcoma. All patients were previously treated with chemotherapy. Results : 120 courses of trabectedin were given (median 4, range 1-20). We were able to assess the response in 24 patients. According to the RECIST criteria responses were as follows: 1 partial response (4%), 12 cases of stable disease (50%), and 11 of progressive disease (46%). The 6-month progression-free survival (PFS) rate was 21%, median PFS was 2.5 months, but in the group of patients who had clinical benefit (PR+SD) the median PFS was 5 months. Tolerance of this treatment was good. In 17 patients adverse events were observed; 5 of them had dose reduction. Mainly there were mild haematological toxicity and hepatotoxicity. 7 patients suffered from grade 3 or 4 toxicity according to CTC v. 4. Conclusion : We showed that trabectedin is effective and well tolerated by patients treated earlier with many lines of chemotherapy for soft tissue sarcoma.